2003
DOI: 10.1590/s1413-70542003000100015
|View full text |Cite
|
Sign up to set email alerts
|

Fontes e doses de molibdênio via foliar em duas cultivares de feijoeiro

Abstract: RESUMO Visando a estudar a resposta de duas cultivares de feijoeiro (Phaseolus vulgaris L.) a fontes e doses de molibdênio via foliar, foram conduzidos três ensaios em um Latossolo Vermelho distroférrico típico (seca e inverno-primavera 97) e um Podzólico MOLYBDENUM SOURCES AND RATES APPLIED ON LEAVES OF TWO COMMON BEAN CULTIVARSABSTRACT Three field experiments were conducted in southern Minas Gerais State, on distrofic Dusky Red Latosol (1997 summer/fall and winter/spring growing seasons) and on a Red Yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
2
0
4
Order By: Relevance
“…Fernandes et al (2005) evaluated the application of foliar Mo and N, in-furrow or sidedress, to no-tillage bean on corn stover and also found no difference for PNP. However, reports of increased PNP in response to Mo application are common in the literature (Pessoa et al, 2001;Silva et al, 2003a;Nascimento et al, 2009). For the year effect, the average PNP was higher in 2010 (Table 3).…”
Section: Resultsmentioning
confidence: 96%
“…Fernandes et al (2005) evaluated the application of foliar Mo and N, in-furrow or sidedress, to no-tillage bean on corn stover and also found no difference for PNP. However, reports of increased PNP in response to Mo application are common in the literature (Pessoa et al, 2001;Silva et al, 2003a;Nascimento et al, 2009). For the year effect, the average PNP was higher in 2010 (Table 3).…”
Section: Resultsmentioning
confidence: 96%
“…Especial atenção tem sido direcionada aos micronutrientes, principalmente ao molibdênio, cuja aplicação, principalmente via foliar, intensifica a coloração verde e a concentração de N das folhas e eleva o número de vagens por planta e o tamanho dos grãos, resultando em significativo incremento de rendimento (AMANE et al, 1994;BERGER et al, 1996;RODRIGUES et al, 1996;ANDRADE et al, 1998;DINIZ et al, 1998;LIMA et al, 1999;ANDRADE et al, 2001). Esse efeito, conforme comprovou Vieira (1994) em experimentos de campo, está relacionado à influência desse micronutriente na atividade das enzimas nitrogenase e redutase do nitrato.…”
Section: Simultaneous Foliar Application Of Molybdenum and Other Agrounclassified
“…Não se tem constatado resposta diferencial de cultivares de feijoeiro ao Mo aplicado via foliar (RODRIGUES et al, 1996), cuja dose ótima tem se situado entre 80 e 90 g ha -1 de Mo (BERGER et al, 1996;RODRIGUES et al, 1996). Para esse mesmo tipo de aplicação, foi constatado ainda que tanto o molibdato de amônio como o molibdato de sódio podem ser indistintamente utilizados (SILVA et al, 1998).…”
Section: Simultaneous Foliar Application Of Molybdenum and Other Agrounclassified
“…It is important for plants in seed production systems to have sufficient molybdenum because the poor pollinization that is associated with molybdenum deficiency may result in lower yield due to lower fertilization rates. Some studies have shown that the yield obtained from plants that have had foliar applications of molybdenum is higher than plants that have not [11]. Since, foliar application of molybdenum has been shown to efficiently increase the seed molybdenum content; however, no improvement has been observed for seed germination and vigor [12] [13].…”
Section: Introductionmentioning
confidence: 99%